Investing for dummies - Tyson, Eric (Eric Kevin). (Hoboken, NJ : John Wiley & Sons, 2011)
Get coverage of all aspects of investing, including how to develop and manage a portfolio; invest in stocks, bonds, mutual funds, and real estate; open a small business; and understand the critical tax implications of your investing decisions.
Investing fundamentals. Exploring your investment choices ; Weighing risks and returns ; Getting your financial house in order before you invest -- Stocks, bonds, and Wall Street. The workings of stock and bond markets ; Building wealth with stocks ; Investigating and purchasing individual stocks ; Exploring bonds and other lending instruments ; Mastering mutual funds ; Choosing a brokerage firm -- Growing wealth with real estate. Investing in a home ; Investing in real estate ; Real estate financing and deal making -- Savoring small business. Assessing your appetite for small business ; Starting and running a small business ; Purchasing a small business -- Investing resources. Selecting investing resources wisely ; Perusing periodicals, radio, and television ; Selecting the best investment books ; Investigating Internet and software resources -- The part of tens. Ten investing obstacles to conquer ; Ten things to consider when weighing an investment sale ; Ten tips for investing in a down market.
Includes index.
Keywords: Investments